Neuropeptide levels in Dercum's disease (adiposis dolorosa) - H. Brorson; B. Fagher; R. Ekman; M. Åberg; H. Svensson; J. Manjer; E. Hansson (PAGEPress Publications, 2012)
Dercum's disease (adiposis dolorosa) is characterised by adiposity and chronic pain in the adipose tissue. It has been proposed that conditions encompassing chronic pain have altered concentrations of neuropeptides involved in pain transmission. The aim of this investigation was to examine whether patients with Dercum's disease have abnormal concentrations of different neuropeptides. In cerebrospinal fluid (CSF) and in plasma (P) from 53 patients with Dercum's disease substance P-like immunoreactivity (SP-LI), neuropeptide Y-like immunoreactivity (NPY-LI), b-endorphin-like immunoreactivity (b-END-LI), calcitonin gene-related peptidelike immunoreactivity (CGRP-LI), met-enkephalin-like immunoreactivity (m-ENK-LI), vasoactive intestinal polypeptide-like immunoreactivity (VIP-LI), somatostatin (SOM-LI), g2-melanocyte-stimulating hormone-like immunoreactivity (g2-MSH-LI), and dynorphin-like immunoreactivity (DYN-LI) were measured. Three of the substances were also measured in a control group. The CSF concentration of SP was statistically significantly lower in the Dercum group than in the control group, whereas NPY-LI and b-END-LI were borderline statistically significantly lower and higher, respectively, in Dercum patients compared to controls. Compared with reference values, CSF-MSH-LI levels were slightly elevated and CSF-NPY-LI levels were slightly lowered in the Dercum group. The other substances in both CSF and plasma were within the reference values with a high degree of statistical significance. In conclusion, altered levels of neuropeptides that have previously been seen in different pain conditions cannot clearly be demonstrated in Dercum's disease.